Making connections: Exploring residents' perspectives on a virtual World Café as a novel approach for teaching Indigenous health issues - Laine-Gossin, Joanne; DeKoven, Samuel; Bordman, Risa (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Implication statementWorld Café is a methodology where small groups of participants rotate around tables for spirited conversations. It creates an environment for sharing and exchange.  Learning about Indigenous healthcare is ideally suited to an intimate discussion format. Adapting the World Café to a virtual platform allowed us to connect disparate learners, encourage peer-to-peer learning, and address inequities in curriculum exposure to different patient groups. Owing to the safe environment, there can be surprising findings too.  In our case, participants identified unconscious biases and recognized the program as a new learning opportunity. Try it and see!